2020
DOI: 10.1101/2020.08.15.20175562
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of COVID-19 on Primary Care Mental Health Services: A Descriptive, Cross-Sectional Timeseries of Electronic Healthcare Records

Abstract: Introduction. There are growing concerns about the impact of the COVID-19 pandemic on mental health. With government-imposed restrictions as well as a general burden on healthcare systems, the pandemic has the potential to disrupt the access to, and delivery of, mental healthcare. Ultimately, this could potentially lead to unmet needs of individuals requiring mental health support. Methods. Electronic healthcare records from primary care psychological therapy services (Improving Access to Psychological Thera… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
(25 reference statements)
1
1
0
Order By: Relevance
“…While the results of our study cannot be generalized to other regions and countries, another study in Germany showed a ca. 27% decline in emergency mental-health service use in one psychiatric hospital, which is comparable with our results, and evidence from studies from the UK and Germany points to the same direction of an overall reduction of inpatient mental healthcare utilization (7)(8)(9)(10)(11). Our study adds new information about a diagnostic shift toward more acutely ill patients.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…While the results of our study cannot be generalized to other regions and countries, another study in Germany showed a ca. 27% decline in emergency mental-health service use in one psychiatric hospital, which is comparable with our results, and evidence from studies from the UK and Germany points to the same direction of an overall reduction of inpatient mental healthcare utilization (7)(8)(9)(10)(11). Our study adds new information about a diagnostic shift toward more acutely ill patients.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, inpatient numbers decreased by 13.6% in the time period March 16-March 30, 2020, compared to the time period February 1-March 15, 2020 (10). Primary-care psychological therapies were even more affected: the number of patients accessing psychological therapies for anxiety and depression in southern England dropped by an average of 55% in the 9 weeks after lockdown (11).…”
Section: Introductionmentioning
confidence: 95%